Polyethylene glycol embedding for immunofluorescence microscopy of plant tissues - Uehara, Koichi (PLANT MORPHOLOGY, 1991)
Polyethylene glycol embedding is an useful method for immunofluorescence microscopy of plant tissues. The dehydration, infiltration and embedding of materials into the polyethylene glycol is easier than the procedures in the usual paraffin method. And the sectioning is easier than cryosectioning. Serial sections of 5-10μm thickness are obtained with a rotary microtome for various tissues of higher plants. This method is useful for immunofluorescence microscopy of microtubules. Microtubule arrangements in elate formation of Equisetum spore are observed by this method.